Market orientation and export performance: the moderation of channel and institutional distance. Issue 2 (9th April 2018) - He, Xinming; Brouthers, Keith D.; Filatotchev, Igor
Abstract : Purpose: Market orientation (MO) has been shown to provide a valuable resource-based advantage in domestic markets. How internationalizing firms from emerging markets can benefit from this capability is more complex while facing institutional distance. The purpose of this paper is to develop and test a theory to suggest that although MO capabilities can enhance export performance, the structure where they are deployed, namely the export channel a firm uses and the market in terms of institutional distance from home, can affect the benefits derived from MO. Design/methodology/approach: With a sample of Chinese exporters and data collected via questionnaire survey, this research uses a multiple regression model to test the hypotheses. Findings: It finds that firms with stronger MO capabilities can improve export performance by using hierarchical channels and by exporting to more institutionally distant markets where MO provides greater value. Originality/value: This research claims to make several important contributions to the literature by providing a better understanding of how firms can successfully deploy MO capabilities when exporting.